2021
DOI: 10.1159/000518952
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Clinical Scores, Immune Cell Modulation, and Microbiota Composition in Allergic Patients with Rhinitis and Asthma Treated with a Probiotic Preparation

Abstract: <b><i>Background:</i></b> Specific drugs and/or immunotherapies are widely used to treat allergies, but drug-induced adverse effects recently led to explore new additional strategies. We studied whether a probiotic preparation (iPROB®; Anallergo SpA, Florence, Italy) is effective in allergic patients and the mechanisms underlying clinical outcomes. <b><i>Methods:</i></b> Eligible patients (<i>n</i> = 28), all suffering from allergic rhinitis with/with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Kang et al ( 19 ) reported that 4 weeks treatment with probiotic NVP-1703 (a mixture of Bifidobacterium longum and Lactobacillus plantarum ) alleviated perennial AR mediated by IgE and IL-10. Torre et al ( 20 ) used iPROB ® probiotic preparation (Anallergo SpA, Florence, Italy) to treat AR patients for 60 days and found a significant decrease in Average Rhinitis Total Symptom Score and improvement in quality of life. In animal studies, Choi et al ( 21 ) found that oral administration of Lactobacillus plantarum (CJLP133 and CJLP243) improved the symptoms and reduced the inflammation in a birch pollen-induced AR mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al ( 19 ) reported that 4 weeks treatment with probiotic NVP-1703 (a mixture of Bifidobacterium longum and Lactobacillus plantarum ) alleviated perennial AR mediated by IgE and IL-10. Torre et al ( 20 ) used iPROB ® probiotic preparation (Anallergo SpA, Florence, Italy) to treat AR patients for 60 days and found a significant decrease in Average Rhinitis Total Symptom Score and improvement in quality of life. In animal studies, Choi et al ( 21 ) found that oral administration of Lactobacillus plantarum (CJLP133 and CJLP243) improved the symptoms and reduced the inflammation in a birch pollen-induced AR mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic managements of constipation are increasingly incorporating prebiotics, probiotics or synbiotics with a view to regulating the intestinal microflora and suppressing both allergic and autoimmune responses [28]. Probiotics/prebiotics/ synbiotics appear to have promising therapeutic effects for improving symptoms in people with asthma and allergies [29][30][31]. However, some mechanisms underlying intestinal microflora mediated regulation of immune responses being described are bacterial strain or metabolite specific, and should not be extrapolated to other probiotics or prebiotics.…”
Section: Discussionmentioning
confidence: 99%
“…During the taxonomic assignment process, only reads with a minimum sequence length that aligned with a reference ≥ 80% and a similarity threshold ≥ 97% were associated with the species taxonomic level. Finally, the software provides absolute and relative abundance tables and three input files (OTU, taxonomy, and metadata) for the subsequent statistical analyses with MicrobiomeAnalyst [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%